Comparative Evaluation of Corneal Endothelium in Patients with Diabetes Undergoing Phacoemulsification - Sahu, Pramod K. (Middle East Afr J Ophthalmol, 2017)
PURPOSE: The purpose of this study is to determine if phacoemulsification with posterior chamber foldable intraocular lens implantation has a greater impact on the corneal endothelium of type 2 diabetic patients as compared to nondiabetic controls. MATERIALS AND METHODS: This study compared the corneal endothelial status in sixty patients with diabetes with good glycemic control and sixty nondiabetic controls before and after (1 week, 1 month, 2 month, and 3 month) uneventful phacoemulsification. Central corneal endothelial cell density, percentage hexagonality, and coefficient of variation were measured using a noncontact specular microscope. Central corneal thickness was taken as a surrogate marker for endothelium functional status. RESULTS: Data were age and sex matched. Patients with diabetes showed significantly higher loss in endothelial cell count as compared to nondiabetic controls. Furthermore, the patients with diabetes showed a slower recovery trend in the endothelial healing response as evidenced by lower change in the coefficient of variation. Significant correlation was found between energy used and change in endothelial count as well as coefficient of variation in nondiabetics only. CONCLUSION: In spite of good glycemic control, patients with diabetes have significantly more endothelial damage in comparison to nondiabetic controls with similar nuclear grading and phaco energy used. This warrants a more careful use of phaco energy in patient with diabetes.